Clinical utility of the KAMRA corneal inlay - Naroo SA; Bilkhu PS (Clinical Ophthalmology, 2016)
Shehzad Anjam Naroo, Paramdeep Singh Bilkhu Ophthalmic Research Group, School of Life & Health Sciences, Aston University, Birmingham, UK Abstract: The treatment of presbyopia has been the focus of much scientific and clinical research over recent years, not least due to an increasingly aging population but also the desire for spectacle independence. Many lens and nonlens-based approaches have been investigated, and with advances in biomaterials and improved surgical methods, removable corneal inlays have been developed. One such development is the KAMRA™ inlay where a small entrance pupil is exploited to create a pinhole-type effect that increases the depth of focus and enables improvement in near visual acuity. Short- and long-term clinical studies have all reported significant improvement in near and intermediate vision compared to preoperative measures following monocular implantation (nondominant eye), with a large proportion of patients achieving Jaeger (J) 2 to J1 (~0.00 logMAR to ~0.10 logMAR) at the final follow-up. Although distance acuity is reduced slightly in the treated eye, binocular visual acuity and function remain very good (mean 0.10 logMAR or better). The safety of the inlay is well established and easily removable, and although some patients have developed corneal changes, these are clinically insignificant and the incidence appears to reduce markedly with advancements in KAMRA design, implantation technique, and femtosecond laser technology. This review aims to summarize the currently published peer-reviewed studies on the safety and efficacy of the KAMRA inlay and discusses the surgical and clinical outcomes with respect to the patient’s visual function. Keywords: presbyopia, refractive surgery, implants, cornea